Ethno-Seasonality and the Social Life among the Highlanders - Poudel, Jiban Mani (Tribhuvan University Journal, 2019)
This paper is about how the seasons and social life of the highlanders are interconnected to each other. It largely concerns on two thematic areas: documentation of emic perspective of naming systems of seasons, and accounting the interconnectedness of seasons and social life of highlanders who live in Nhāson, a small mountain valley located in the central Himalayan region of Nepal. Information is based on 9 months place-specific ethnography in different periods from the years 2012 to 2018. Informal conversation with the local people and observation of the physical environment and socio-cultural life were the key sources of understanding the interconnectedness of seasons and social life of the highlanders. Findings show seasons are the parts of social life for the highlanders. The change of seasons from one season to another is not just a matter of change in weather patterns and the associated changes in physical environment of the surrounding but it is also a change in social life. Therefore, physical and social seasonality go side by side as rhythms which are the integral parts of culture and social life of highlanders. Moreover, local’s definition of seasons is cultural specific and place-specific that challenges state defined universal definition of seasons and force to rethink it differently.